Computerized respiratory sound analysis in people with dementia: a first-step towards diagnosis and monitoring of respiratory conditions. (27th October 2016) - Rocha, Vânia; Melo, Cristina; Marques, Alda
Abstract: Computerized respiratory sound analysis has been shown to be an objective and reliable way to assess respiratory diseases. However, its application in non-collaborative populations, such as people with dementia, is still unknown. Therefore this study aimed to characterize normal and adventitious respiratory sounds (NRS; ARS) in older people with and without dementia. A cross-sectional study including two groups of 30 subjects with dementia and 30 subjects without dementia was performed. Digital auscultation was used to record NRS and ARS per breathing-phase (inspiration/expiration) at trachea and thorax. Frequency at percentiles 25, 50 and 75, frequency at maximum-intensity, maximum-intensity ( I max ) and mean-intensity ( I mean ) characterized NRS. Crackle number, frequency, initial-deflection-width, 2cycle-duration, and largest-deflection-width and wheeze number, frequency and occupation-rate characterized ARS. Groups were similar in socio-demographics, except for anthropometrics. No significant differences were found between groups in NRS frequency or ARS at trachea or thorax. Significant lower I max (inspiration: 36.88(29.42;39.92) versus 39.84(36.50;44.17) p = 0.007; expiration: 34.51(32.06;38.87) versus 42.33(36.92;44.98) p < 0.001) and I mean (inspiration: 15.23(12.08;18.60) versus 18.93(15.64;21.82) p = 0.003 and expiration: 14.57(12.08;18.30) versus 18.87(15.64;21.44) p = 0.001) at trachea and higher I mean (inspiration: 17.29(16.04;19.31) versus 16.45(15.05; 18.79) p = 0.005 and expiration: 16.71(15.31;18.56) versus 16.38(14.40;17.85) p = 0.011) at thorax were found in subjects with dementia when compared with subjects without dementia. To conclude, people with and without dementia had similar NRS and ARS characteristics, except for NRS intensity. Computerized respiratory sound analysis was feasible in a non-collaborative population. Further research is needed to enhance the use of respiratory acoustics in non-collaborative populations, with strong potential to be applied in different settings for diagnosis and monitoring purposes.